Palatally Positioned Two Mesiodens: A Case Report - Agrawal, Sudhanshu; Halwai, Hemant Kumar (Orthodontic Journal of Nepal, 2012)
Mesiodens is a supernumerary tooth located in the anterior maxilla, placed palatally, labially or in between the maxillary central incisors. It may be single or paired, erupted or impacted and at times even inverted. This case report describes a palatally positioned two mesiodens in an 8-year-old male. The clinical and radiographic appearance and therapeutic considerations are presented. The purpose of this article is to alert the clinician to the importance of radiographic localization prior to surgical intervention, because in some instances a labial surgical approach is preferred over the traditional palatal technique. In this case a labial surgical approach was utilized which allowed for greater conservation of alveolar bone and improved access during removal of the mesiodens teeth.